An innately dangerous balancing act: intestinal homeostasis, inflammation, and colitis-associated cancer. - Asquith, M; Powrie, F (2010)
Inflammatory bowel disease (IBD) is characterized by dysregulated immune responses to the intestinal microbiota, and by chronic intestinal inflammation. Several recent studies demonstrate the importance of innate microbial recognition by immune and nonimmune cells in the gut. Paradoxically, either diminished or exacerbated innate immune signaling may trigger the breakdown of intestinal homeostasis, leading to IBD and colitis-associated cancer (CAC). This dichotomy may reflect divergent functional roles for immune sensing in intestinal epithelial cells and leukocytes, which may vary with distinct disease mechanisms.